2020
DOI: 10.3892/etm.2020.9362
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum VEGF, IL‑1 and TNF‑α in the treatment of thromboangiitis obliterans by revascularization

Abstract: Effect of revascularization in the treatment of thromboangiitis obliterans (TAO) and the predictive value of serum vascular endothelial growth factor (VEGF), interleukin-1 (IL-1) and tumor necrosis factor-α (TNF-α) of risk factors of amputation were investigated. From April 2012 to August 2015, a total of 117 patients with TAO admitted to the First Hospital of Lanzhou University were selected. Patients treated with revascularization combined with prostaglandin sodium and cilostazol were enrolled in group A (67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…All articles were patient-based and 7 articles were conducted in Iran, 4 in China and one in Korea. Systematic reviews and metaanalyses were not available, all clinical trials were not ethically prohibited, and randomized trials were assessed based on Consort checklists (11,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Results and Ndingsmentioning
confidence: 99%
See 1 more Smart Citation
“…All articles were patient-based and 7 articles were conducted in Iran, 4 in China and one in Korea. Systematic reviews and metaanalyses were not available, all clinical trials were not ethically prohibited, and randomized trials were assessed based on Consort checklists (11,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Results and Ndingsmentioning
confidence: 99%
“…o TNF reduce reperfusion in TOA by tobacco We concepted that cytokine induced TOA, one of the most effective in ammatory parameters in Buerger is TNF. It can be said that the hottest discussion in our available studies has been TNF-α, along with IL-6 and IL-1 (23,34). The roles of TNF include involvement in in ammation, muscle weakness, and pain in TOA.…”
Section: Results and Ndingsmentioning
confidence: 99%
“…Pro-angiogenic therapy using VEGF may be useful in ischemic diseases such as stroke, myocardial ischemia and coronary artery disease [ 49 ]. VEGF and IL‑1 act inversely as the risk factors in the treatment of thromboangiitis obliterans by revascularization [ 50 ], and IL-1 may induce VEGF production in chondrocytes through distinct signaling pathways [ 51 ]. VEGF has the ability to increase ICAM-1 expression in the retinal vasculature and ICAM-1 can mediate VEGF-induced vascular permeability and nonperfusion [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Vascular endothelial growth factor (VEGF), a natural growth factor encoded by the VEGFA gene, participates in physiological processes relating to blood vessels and metabolism, including blood vessel growth, endothelial cell destruction, oxygen and glucose delivery, and blood vessel permeability. 6,7 Considering vascular factors and the role of VEGF in AD and VaD, numerous studies have evaluated the diagnostic capability of VEGF for different types of dementia in humans. Some studies have found significant differences in blood or cerebrospinal fluid (CSF) levels between AD or VaD subjects and cognitively normal (CN) subjects, suggesting the possibility of diagnosing these two forms of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), a natural growth factor encoded by the VEGFA gene, participates in physiological processes relating to blood vessels and metabolism, including blood vessel growth, endothelial cell destruction, oxygen and glucose delivery, and blood vessel permeability 6,7 . Considering vascular factors and the role of VEGF in AD and VaD, numerous studies have evaluated the diagnostic capability of VEGF for different types of dementia in humans.…”
Section: Introductionmentioning
confidence: 99%